Cloud Computing Deployment Models: A Comparative Study (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing has become the embraced in the computer world. Cloud implementation is the process  of creating a virtual computing environment. Deployment in  the cloud provides organizations with flexible and scalable  virtual computing resources. A cloud deployment model is  the type of architecture in which a cloud system is deployed.  These models differ in terms of administration, ownership,  access control, and security protocols. This paper describes  the different types of cloud computing service models and  deployment models; it also gives us a comparative study of  various clouds using many factors. The comparison is  simply based on various factors such as reliability, cost, data  control, workload, performance, and many other cloud  parameters.
Keywords: Deployment model; Service model; Public cloud; Private cloud; Hybrid cloud; Inter-Cloud; Federation cloud; Multi cloud